2011
DOI: 10.7863/jum.2011.30.11.1499
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Malignant From Benign Thickening of the Gallbladder Wall by the Use of Acoustic Radiation Force Impulse Elastography

Abstract: Elastography is an accurate technique for differentiating between benign and malignant gallbladder wall thickening and can be combined with sonography as the prime imaging tool for diagnosing gallbladder carcinoma at an early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…There are studies that suggest elastography can help in differentiating malignant and benign. 48,49 With this method, inflammatory tissue can be differentiated from the masses of epithelial tissue. Teber et al evaluated the feasibility of elastography in a preliminary report.…”
Section: Figmentioning
confidence: 99%
“…There are studies that suggest elastography can help in differentiating malignant and benign. 48,49 With this method, inflammatory tissue can be differentiated from the masses of epithelial tissue. Teber et al evaluated the feasibility of elastography in a preliminary report.…”
Section: Figmentioning
confidence: 99%
“…In a study by Kapoor et al [13], a mean shear wave velocity of 3.41 m/s (95% confidence interval, 3.1–3.7 m/s) was seen in patients with gallbladder carcinoma. At a cut-off value of 2.7 m/s, elastography showed overall accuracy of 92.8% with sensitivity and specificity of 100% and 91.3%, respectively, for diagnosing gallbladder carcinoma.…”
Section: Focal or Diffuse Asymmetric Wall Thickeningmentioning
confidence: 99%
“…They reported a diagnostic performance that had a sensitivity and specificity of 100 and 91.3 %, respectively, and the cutoff value for diagnosing gallbladder carcinoma based on the mean shear wave velocity was 3.41 m/s ( P  < 0.0001), and the area under the curve was 0.92. They concluded that elastography was a promising modality for differentiating between benign and malignant gallbladder wall thickening and should be used in combination with B-mode US [72]. In other biliary diseases, elastography has been reported to be useful as a noninvasive marker for primary biliary cirrhosis or the prediction of upper GI varices in children with biliary atresia [7380].…”
Section: Elastography For the Biliary Systemmentioning
confidence: 99%